Morphoagronomic and Phenological Characteristics of Roselle (Hibiscus sabdariffa L.) Grown in Sudano-Sahelian Zone of Cameroon - Taffo Junior Baudoin Wouokoue; Francois Romain Fouelefack; Nguenjou Carole Leticia Liejip; Wanchebe Eleonore Biakdjolbo; Tchinda Elodie Mafouo (International Journal of Agronomy)
Hibiscus sabdariffa (HS) is a plant that has been used traditionally as a food in the preparation of herbal drinks, hot and cold beverages. Identifying and characterising HS accessions are important for its better exploitation. This study aimed to describe the morphoagronomic and phenological characteristics of Roselle accessions grown in the Sudano-Sahelian zone of Cameroon. Six accessions of HS were sown in a randomised complete block design (RCBD) with three replications. They were evaluated to find out their similarities and differences in qualitative and quantitative traits. Phenological data were monitored weekly for 5 months. Significant differences were observed within and between accessions for both morphological and agronomic characters. Five accessions have leaves shape with 2–5 lobs and produced reddish calyces with different degrees of redness, whereas accession HS-2 has white calyces colour and leaves shape of 3 lobs. Accession HS-1 was the tallest (103.33 ± 15.38 cm) and had the highest number of fruits/plants (64.83 ± 33.26). The highest dry calyces weight/plant was found in HS-5 (11.61 ± 5.27 g) accessions, while that of dried seeds weight were recorded in HS-5 (13.88 ± 4.87 g/plant). Accessions HS-1, HS-2, HS-3 and HS-5 flowered in about 2 months and harvested in less than 4 months, whereas HS-4 and HS-6 were late about three to 4 months to flower and took almost 5 months to harvest. HS-5, HS-3 and HS-2 accessions have showed the precocity of maturity time and present the highest calyces and seeds yields. This work highlights the high-yielding accessions, HS-3 and HS-5 which are less common, and can be also exploited for their agronomic potential. The variation between accessions of HS shows the potential of this germplasm for use in qualitative and quantitative genetic improvement of Roselle.